An online family-based self-monitoring and goal-setting intervention to improve children's physical activity: the FRESH feasibility trial and three-arm pilot RCT - Esther MF van Sluijs; Helen E Brown; Emma Coombes; Claire Hughes; Andrew P Jones; Katie L Morton; Justin M Guagliano (NIHR Journals Library, 2021)
Background: Family-based physical activity promotion presents a promising avenue for promoting whole-family physical activity, but high-quality research is lacking. Objectives: To assess the feasibility, acceptability and preliminary effectiveness of FRESH (Families Reporting Every Step to Health), a child-led online family-based physical activity intervention; and to identify effective and resource-efficient family recruitment strategies. Design: The project consisted of (1) a randomised feasibility trial, (2) a randomised controlled pilot trial and (3) a systematic review and Delphi study. Setting: Norfolk/Suffolk counties, UK. Participants: Families, recruited from schools, workplaces and community settings, were eligible to participate if one child aged 7-11 years and one adult responsible for their care provided written consent; all family members could participate. Interventions: The FRESH intervention, guided by self-determination theory, targeted whole families and was delivered via an online platform. All family members received pedometers and were given website access to select family step challenges to 'travel' to target cities around the world, log steps, and track progress as they virtually globetrotted. Families were randomised to FRESH intervention, pedometer-only or control arm. Main outcome measures: Physical (e.g. blood pressure), psychosocial (e.g. family functioning) and behavioural (e.g. device-measured family physical activity) measures were collected at baseline and at 8- and 52-week follow-up. A mixed-methods process evaluation assessed the acceptability of the intervention and evaluation. Data sources review: Systematic search of four databases (Cochrane Library, PubMed, PsycINFO and SCOPUS). Review methods: Articles were screened in duplicate, and data extraction was fully checked. Academic experts participated in the three-round Delphi study. Data were combined to identify effective and resource-efficient family recruitment strategies. Inclusion criteria: Included generally healthy school-aged children and at least one adult; intervention attempted to change physical activity, sedentary behaviour, screen use, diet, or prevent overweight/obesity in multiple family members; presented relevant measure of effect in children and adults. Results: The feasibility study (12 families, 32 participants; 100% retention at 8 weeks) demonstrated the feasibility and acceptability of FRESH, but highlighted that adaptations were required. Of 41 families recruited in the pilot study (149 participants), 98% and 88% were retained at the 8-week and 52-week follow-up, respectively. More children in the FRESH arm self-reported doing more family physical activity, and they thought that FRESH was fun. There were no notable between-group differences in children's outcomes. Change in moderate to vigorous physical activity at 8 weeks favoured FRESH intervention adults [vs. control: 9.4 minutes/week (95% confidence interval 0.4 to 18.4) vs. pedometer only: 15.3 (95% confidence interval 6.0 to 24.5)], and was stronger in fathers, but this was not maintained. In 49 included studies, apart from recruitment settings and strategies used (reported in 84% and 73% of the studies, respectively), recruitment details were scarce. School-based recruitment was predominant. The Delphi study identified a wide range of recruitment settings and strategies. Limitations: Recruitment was the main limitation of the FRESH studies; generalisability of the proposed recruitment strategies may be limited. Conclusions: This study has demonstrated the feasibility and acceptability of the FRESH intervention. However, we failed to recruit the target sample size and were unable to demonstrate a signal of effectiveness. Future research should employ a multifaceted recruitment approach. Future work: Further refinements to intervention delivery and recruitment methods should be investigated. Study registration: Current Controlled Trials ISRCTN12789422 and PROSPERO CRD42019140042. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 9, No. 9. See the NIHR Journals Library website for further project information.